(untitled) (Research Announcements "Heritage BG", 2025)
The article analyzes the growing influence of non-governmental organizations (NGOs) and their implementations in the policies on international, European and national levels. The role and influence of NGOs in the processes of creating and implementing policies related to the protection of cultural heritage is growing. This is explained both by the democratic processes in the management and implementation of policies, and by the growing need for active civic participation in these processes. Positive examples for the role of non-governmental organizations in non-formal education as an alternative form of education related to the preservation of the intangible cultural heritage are given. Good practices and partnerships of various cultural institutions and NGOs from Bulgaria and abroad are presented. References: Ivanova 2013: Nematerialno nasledstvo i obshtoevropeyski kulturni politiki. Bulgarian Folklor, No. 1, 7-15. Nenova 2021: Opazvane na kulturnoto nasledstvo v chitalishtata prez XX i XXI v. – Zakonodatelni dokumenti i praktiki. Internet sources: Slavov 2009:59, Slavov, Atanas. Uchastie na nepravitelstvenite organizacii v protsesite na vzemane na reshenya. Prawn analiz, sravnitelen analiz, strategicheski dokument. Sofia. http://2020.eufunds.bg/bg/0/96/Project/Activities?contractId=yf5K4H%2FCSTE%3D&isHistoric=False Feld 1988:222, Feld, Jordan –in Martens, Kerstin 1999. Тhe role of NGOs in the UNESCO System – Transnational Associations, Issue 2/1999, 68-82. https://uia.org/archive/role-ngos-unesco (28.05.2022) Kotschnig 1957: Kotschnig, Walter. Education, Science and Culture. – Asher, Robert E. (Ed.), The United Nations and Promotion of the General Welfare (Washington: Brooking Institution), 550-80. – Ιn Martens, Kerstin 1999. Тhe Ρole of NGOs in the UNESCO System – In: Transnational Associations, Issue 2/1999, 68-82. https://uia.org/archive/role-ngos-unesco Martens 1999: Martens, Kerstin. Тhe Ρole of NGOs in the UNESCO System. –Transnational Associations, Issue 2/1999, 68-82. https://uia.org/archive/role-ngos-unesco (04.04.2022) http://bcnl.org/analyses/obshtestveni-naglasi-kam-grazhdanskite-organizatsii-202-0.html http://chwb.org/?lang=en http://ciino.ngobg.info/ https://ich.unesco.org/en/ngo-centers-and-institutions-00329#ngos-and-the-2003-convention http://www.heritagevolunteers.eu/EuropeanHeritage http://infopass.eu/cause/images/11_Kodex_dobri_praktiki.pdf https://kab-so.com/archives/15502 https://newspaper.kultura.bg/bg/article/view/23340 https://www.strategy.bg/FileHandler.ashx?fileId=1292 https://www.unesco-centerbg.org/wp-new/wp-content/uploads/2020/02/Narychnik-1-final3.pdf http://staraplanina.meshtrango.com/ https://trainingfactory.biz/polezno-info/neformalno-obrazovanie/ http://bcnl.org/analyses/obshtestveni-naglasi-kam-grazhdanskite-organizatsii-2020.html